Growth Hormone and Reproduction: Lessons Learned From Animal Models and Clinical Trials - Dosouto, Carlos; Calaf, Joaquim; Polo, Ana; Haahr, Thor; Humaidan, Peter (Frontiers in Endocrinology, 2019)
Growth Hormone (GH) has been considered as a therapeutic option to increase the number of growing follicles during Assisted Reproductive Technology (ART) for more than 30 years. In this review the biological rationale for therapeutic GH usage is explained through evidence in animal models, aiming to put this into a clinical context. First, we explain the GH—Insulin like Growth Factor (IGF)-1—gonadal axis and its role in reproduction. Evidence suggests that GH can stimulate the secretion of IGF1 not only in the liver but also in the peripheral target structures, including the ovary. Moreover, IGF-1 can be secreted locally under the influence of stimuli other than GH. In the case of the ovary, steroid hormones, gonadotropins or the combination of both seems to be involved. Even more interesting, the ovary itself can secret GH locally and exert a paracrine action modulating the intracellular signaling pathway of GH, i.e., not by the systemic pathway where GH binds to the extracellular domain of the GH receptor. Finally, these aspects from animal models are put into clinical perspective by discussing results and shortcomings of studies and meta-analyses in order to put forth the state-of-the-art rationale for therapeutic GH usage in modern ART.